Forensic estimation of medical aid rendered to the patients died with traumatic brain injury (on evidences of forensic expertise) - A. O. Pletnetskaya (Kazimierz Wielki University, 2016)
Pletnetskaya A. O. Forensic estimation of medical aid rendered to the patients died with traumatic brain injury (on evidences of forensic expertise). Journal of Education, Health and Sport. 2016;6(8):607-613. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61022 http://ojs.ukw.edu.pl/index.php/johs/article/view/3791       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016.     UDC 340.6: 614.23/.25: 616-036.8   FORENSIC ESTIMATION OF MEDICAL AID RENDERED TO THE PATIENTS DIED WITH TRAUMATIC BRAIN INJURY (ON EVIDENCES OF FORENSIC EXPERTISE)   A. O. Pletnetskaya   P.L.ShchupikNationalMedicalAcademyof Postgraduate Training,Kiev,Ukraine   Summary Traumatic brain injury is a general reason of death. The objective: to conduct a forensic analysis of the defects of medical care  and clarify their causes in TBI's victims. The research was done according to expert panel evidences (EPE) of several bureaus of forensic medical examination for ten years (2006-2016).The examinations related to the 6129 corpses of TBI victims. 30 EPE examinations were selected for the further analysis. the data were distributed on year, forensic bureau, date of death, time of death, the presence or absence of comorbidity, sex and age of the deceased, date and time of injury, date and time of ambulance arrival, type of  medical establishment (municipal clinical, central district hospital, regional hospital, specialized, e. g. research institute of neurosurgery), the time of delivery to the hospital, time of the medical aid start, blood pressure systolic/diastolic, heart rate, patient's condition, consciousness, presence of described injuries, examination by experts, additional examinations, operation, its time, clinical diagnosis (basic), clinical diagnosis (secondary), defects of medical care, their number, type, cause, timeliness of medical care, presence/ absence of cause-effect relation of defect with adverse effects. The data obtained were subject to statistical analysis with standard methods of descriptive statistics. Gross defects of medical care which in some or other way influenced the result were found in 13 cases, i.e. almost half of cases. In 7.7% of cases took place improper provision (action); the failure to provide medical attention (inactivity) were observed in 92.7% (12 cases). A direct cause-and-effect relationship between defect of medical care and adverse outcome was found in 53.84% of cases.   Key words: traumatic brain injury, expert panel evidence, forensic medical examination.